Mark–recapture of Cerambyx welensii in dehesa woodlands: dispersal behaviour, population density, and mass trapping efficiency with low trap densities - Torres-Vila, Luis M.; Sánchez-González, Álvaro; Merino-Martínez, Jesús; Ponce-Escudero, Francisco; Conejo-Rodríguez, Yolanda; Martín-Vertedor, Daniel; Ferrero-García, Juan J. (Entomologia Experimentalis et Applicata, 2013)
The longhorn beetle, Cerambyx welensii Küster (Coleoptera: Cerambycidae), is an emerging pest involved in oak decline episodes in dehesa open woodlands. Larvae are xylophagous and cause considerable physiological, mechanical, and structural damages to trees. Chemical and biological control are currently unsatisfactory. Recent research has shown that mass trapping with a high density of baited traps (40 traps ha−1) could be useful to manage C. welensii populations, although such a trap density was too high to be cost-effective. In this 2-year study (2010–2011) we investigated with mark–recapture methods in a large plot (1) the flight dispersal behaviour, (2) the adult population density, and (3) the efficiency of mass trapping at two low trap densities (one or four traps ha−1). Results indicated that many adults were sedentary (60%) but flying adults displayed a strong propensity to move, both sexes dispersing on average more than 200 m and one male and one female flying at least 540 and 349 m, respectively. Recapture rates were high (0.26–0.35) and population density was estimated to be 6–22 adults ha−1 with maximum likelihood models. Trapping efficiency ranged 48–61% with no significant effect of trap density or year. We conclude that results were not satisfactory enough to recommend mass trapping with low trap densities as control method for C. welensii and that more research is still required on the technical, ecological, and behavioural factors affecting control efficiency.
From Duplicate 1 ( Mark–recapture of Cerambyx welensii in dehesa woodlands: dispersal behaviour, population density, and mass trapping efficiency with low trap densities - Torres-Vila, Luis M.; Sánchez-González, Álvaro; Merino-Martínez, Jesús; Ponce-Escudero, Francisco; Conejo-Rodríguez, Yolanda; Martín-Vertedor, Daniel; Ferrero-García, Juan J. )From Duplicate 1 ( Mark–recapture of Cerambyx welensii in dehesa woodlands: dispersal behaviour, population density, and mass trapping efficiency with low trap densities - Torres-Vila, Luis M.; Sánchez-González, Álvaro; Merino-Martínez, Jesús; Ponce-Escudero, Francisco; Conejo-Rodríguez, Yolanda; Martín-Vertedor, Daniel; Ferrero-García, Juan J. )
Keywords: cerambycidae; Coleoptera; Fagaceae; Holm oak; longhorn beetle; ml secr models; Oak decline; open woodland; pest control

Mark–recapture of Cerambyx welensii in dehesa woodlands: dispersal behaviour, population density, and mass trapping efficiency with low trap densities - Torres-Vila, Luis M; Sánchez-González, Álvaro; Merino-Martínez, Jesús; Ponce-Escudero, Francisco; Conejo-Rodríguez, Yolanda; Martín-Vertedor, Daniel; Ferrero-García, Juan J (Entomologia Experimentalis et Applicata, 2013)
The longhorn beetle, Cerambyx welensii Küster (Coleoptera: Cerambycidae), is an emerging pest involved in oak decline episodes in dehesa open woodlands. Larvae are xylophagous and cause considerable physiological, mechanical, and structural damages to trees. Chemical and biological control are currently unsatisfactory. Recent research has shown that mass trapping with a high density of baited traps (40 traps ha−1) could be useful to manage C. welensii populations, although such a trap density was too high to be cost-effective. In this 2-year study (2010–2011) we investigated with mark–recapture methods in a large plot (1) the flight dispersal behaviour, (2) the adult population density, and (3) the efficiency of mass trapping at two low trap densities (one or four traps ha−1). Results indicated that many adults were sedentary (60%) but flying adults displayed a strong propensity to move, both sexes dispersing on average more than 200 m and one male and one female flying at least 540 and 349 m, respectively. Recapture rates were high (0.26–0.35) and population density was estimated to be 6–22 adults ha−1 with maximum likelihood models. Trapping efficiency ranged 48–61% with no significant effect of trap density or year. We conclude that results were not satisfactory enough to recommend mass trapping with low trap densities as control method for C. welensii and that more research is still required on the technical, ecological, and behavioural factors affecting control efficiency.
From Duplicate 1 ( Mark–recapture of Cerambyx welensii in dehesa woodlands: dispersal behaviour, population density, and mass trapping efficiency with low trap densities - Torres-Vila, Luis M.; Sánchez-González, Álvaro; Merino-Martínez, Jesús; Ponce-Escudero, Francisco; Conejo-Rodríguez, Yolanda; Martín-Vertedor, Daniel; Ferrero-García, Juan J. )
Keywords: cerambycidae; Coleoptera; Fagaceae; Holm oak; longhorn beetle; ml secr models; Oak decline; open woodland; pest control